Esigibilità penale e pluralità delle culture - Incampo, Antonio (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2020)
The end of totalitarianisms in the twentieth century and the age of globalization have overshadowed the traditional question about the adequacy of punishments, placing two completely new ones and most likely destined to definitively change the very concept of criminal law. The first: What punishments for citizens beyond the State? The second: What punishments for the foreigners on this side of the State? Law has today the urgency to consider man as a true subject of law in a world that has more and more a common destiny. The unity of punishment is its new frontier. Keywords: Totalitarianisms, Globalization, Mankind, Cultural Differences, Human Rights, Criminal Law, Punishment.